Mental Fatigue and Basketball Performance: A Systematic Review - Cao, Shudian; Geok, Soh Kim; Roslan, Samsilah; Sun, He; Lam, Soh Kim; Qian, Shaowen (Frontiers in Psychology, 2022)
Mental fatigue (MF) is a psycho-biological state that impairs sports-related performances. Recently, it has been proved that MF can affect basketball performance. However, a systematic overview detailing the influences of MF on basketball performance is still lacking. This study aims to investigate the effects of MF on the physical, technical, tactical, and cognitive performance of basketball. We used the databases of PubMed, Web of Science, SPORTDiscus, Scopes, and CKNI for articles published up to 31 May 2021. The articles included in this study were projected to test whether MF influences basketball athlete performance. Only experimental design studies were selected, and the control condition was without MF. Finally, six articles fit the inclusion criteria. The results imply that MF impairs the technical aspects of basketball (free throws, three-point shots, and total turnover) and the players’ cognitive (take-the-first [TTF] heuristics and decision-making) performance, which results in athletes not using their techniques skillfully and being unable to make practical decisions during critical points in the game. In addition to that, the influences of MF on physical and tactical performance have not been studied. Further studies should look into comprehensive research on the influences of MF on basketball athlete performance, especially on a player’s physical and tactical performance. The results of this overview show that researchers tend to investigate the influences of MF on small-sided games (SSGs) or basketball tests (e.g., free-throw tests) rather than actual competition. Finally, more recovery strategies should be found to help basketball players recover from MF.